Towards sugar-derived polyamides as environmentally friendly materials1. Issue 22 (14th June 2015) - Wroblewska, Aleksandra; Zych, Arkadiusz; Thiyagarajan, Shanmugam; Dudenko, Dmytro; van Es, Daan; Hansen, Michael Ryan; Koning, Cor; Duchateau, Rob; Jasinska-Walc, Lidia
<x xml:space="preserve">Abstract</x> As part of our ongoing study investigating isohexide-based polyamides, we have synthesized isosorbide(bis(propan-1-amine)) (DAPIS) and studied its reactivity in the polymerization towards fully biobased polyamides.